2015
DOI: 10.1186/s12864-015-1721-z
|View full text |Cite
|
Sign up to set email alerts
|

A GWAS assessment of the contribution of genomic imprinting to the variation of body mass index in mice

Abstract: BackgroundGenomic imprinting is an epigenetic mechanism that can lead to differential gene expression depending on the parent-of-origin of a received allele. While most studies on imprinting address its underlying molecular mechanisms or attempt at discovering genomic regions that might be subject to imprinting, few have focused on the amount of phenotypic variation contributed by such epigenetic process. In this report, we give a brief review of a one-locus imprinting model in a quantitative genetics framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Trait-associated SNPs with imprinting effects can be detected by linkage analysis and GWASs. Models to do such analyses are presented in Mantey et al (2005) and Hu et al (2015).…”
Section: Dominance and Imprintingmentioning
confidence: 99%
“…Trait-associated SNPs with imprinting effects can be detected by linkage analysis and GWASs. Models to do such analyses are presented in Mantey et al (2005) and Hu et al (2015).…”
Section: Dominance and Imprintingmentioning
confidence: 99%
“…Our model cleanly separates imprinting from the standard (additive and dominance) genetic effects, providing for a clear understanding of how imprinting contributes to both nonheritable and heritable variation and, hence, evolutionary processes. While a similar formulation of genetic effects has been used by others to partition variation (de Koning et al 2002;Shete and Amos 2002;Mantey et al 2005;Álvarez-Castro 2014;Hu et al 2015), these studies have not examined the consequences of imprinting for evolution. A previous study has evaluated how imprinting impacts the responses to selection (Santure and Spencer 2011), but because it is built on a nonorthogonal model of genetic effects it did not allow the effects of imprinting and dominance to be disentangled.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that, with imprinting, the mean genotypic (and phenotypic, assuming no environmental effect on phenotype) value for the population ( w) is equivalent to that under standard Mendelian expression (de Koning et al 2002;Spencer 2002;Hu et al 2015):…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations